2020
DOI: 10.3390/diagnostics10110860
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches in the Study of the Pathogenesis of Urethral Pain Syndrome

Abstract: Introduction: Urethral pain syndrome (UPS) is still a pathology in which the diagnosis is formulated as a “diagnosis of exclusion”. The exact pathogenetic mechanisms are not yet fully understood and clear recommendations for the prevention and treatment of UPS are absent. Methods and Participants: A clinical and laboratory evaluation of 55 patients with established UPS included history taking, basic laboratory tests (e.g., complete blood count and clinical urine test), physical examination, uroflowmetry, and c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…The article by Streltsova and colleagues is dedicated to the targeted study of female urethral tissues (their elasticity and the condition of the epithelial and connective tissue layers) in urethral pain syndrome (UPS). The results showed that the introduction of new CP OCT technology in conjunction with transvaginal compression ultrasound will allow for in vivo verification of structural changes in lower urinary tract tissues at their architectonics level and will provide more information about basic elements of the UPS pathogenesis [ 5 ].…”
mentioning
confidence: 99%
“…The article by Streltsova and colleagues is dedicated to the targeted study of female urethral tissues (their elasticity and the condition of the epithelial and connective tissue layers) in urethral pain syndrome (UPS). The results showed that the introduction of new CP OCT technology in conjunction with transvaginal compression ultrasound will allow for in vivo verification of structural changes in lower urinary tract tissues at their architectonics level and will provide more information about basic elements of the UPS pathogenesis [ 5 ].…”
mentioning
confidence: 99%
“…Вторым фактором, влияющим на тонус сосудов и на состояние слизистой оболочки уретры, является гуморальный [20,21]. Ранее методом КП ОКТ в нашей работе [22] было показано, что изменения эпителия в шейке МП и уретре (гиперплазия или атрофия) зависят от гормонального фона женщин: у женщин репродуктивного возраста встречаются в 44,4% случаев, в постменопаузальном периоде -в 93,3% наблюдений.…”
Section: Discussionunclassified
“…The rational of UPS treatment hypothesis with Caressflow® (Caress Flow Srl, Bologna, Italy) is substantiated by the clinical study of Streltsova et al [26]: Accordingly with her observation, the urethra and the bladder are embryologically and physiologically joined in "the painful bladder syndrome" [27] and the common connective tissue matrix of both the structures with its protective and trophic functions, displays a mechanosensitive signalling system [28], [29] and might be responsible of the disease. The authors in their utmost interesting paper describe also the routinary diagnostic methods, such as ultrasound (US) and uroflowmetry, but also US elastography and cross-polarization optical tomography (CP OCT); the last one seems be the most appealing method to detect UPS, on an investigational basis, being able to explain the fine neurovascular disorder of urethra [30], [31], [32], [33], [34].…”
Section: Introductionmentioning
confidence: 99%
“…The authors in their utmost interesting paper describe also the routinary diagnostic methods, such as ultrasound (US) and uroflowmetry, but also US elastography and cross-polarization optical tomography (CP OCT); the last one seems be the most appealing method to detect UPS, on an investigational basis, being able to explain the fine neurovascular disorder of urethra [30], [31], [32], [33], [34]. Streltsova et al compared transvaginal US (TVUS) with compression elastography and CP OCT in 55 patients with UPS against 14 control healthy patients [26]. TVUS showed enlargement of the internal lumen of the upper third of the urethra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation